2024
DOI: 10.1111/dme.15301
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the perceptions and experiences of participants and healthcare professionals in the DiRECT‐Australia type 2 diabetes remission service

Ritesh Chimoriya,
Freya MacMillan,
Michael Lean
et al.

Abstract: BackgroundThe UK Diabetes Remission Clinical Trial (DiRECT) study was replicated in an Australian primary care setting. This qualitative study aimed to explore and understand the perceptions and experiences of both participants and healthcare professionals (HCPs) involved in the DiRECT‐Australia Type 2 Diabetes Remission Service.MethodsAll participants and HCPs delivering the service were invited to participate in semi‐structured interviews via online videoconferencing. The interview guides explored perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Previous research has found DiRECT to be an acceptable approach for weight loss among people with type 2 diabetes [ 14 , 15 , 16 ]. In line with the process of adaptation we have reported, Rehackova et al describe a “fluctuation of experience” within the original DiRECT-UK trial [ 14 ] (p. 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has found DiRECT to be an acceptable approach for weight loss among people with type 2 diabetes [ 14 , 15 , 16 ]. In line with the process of adaptation we have reported, Rehackova et al describe a “fluctuation of experience” within the original DiRECT-UK trial [ 14 ] (p. 4).…”
Section: Discussionmentioning
confidence: 99%
“…The participants in our study and the DiRECT-UK trial each identified new and reoccurring challenges requiring resilience and tailored support. In fact, many of the experiences described by our participants appear universal: a desire for weight loss and better health as a stimulus for participation in a total diet replacement intervention [ 14 , 15 , 16 , 46 , 47 ]; the abrupt but worthwhile adjustment to a total diet replacement regimen [ 14 , 15 , 16 , 46 ]; professional support as a source of accountability [ 14 , 15 , 48 ]; drawing on rapid and early weight loss as an important motivator [ 14 , 15 , 48 ]; navigating the “disruption to adaptation” [ 14 ] (p. 7) posed by food reintroduction; the challenging realities of weight loss maintenance [ 14 , 16 , 46 , 47 , 48 , 49 ]; and the development of “behavioural autonomy” [ 49 ] (p. 956). As we identified, the timing and intensity of the challenges faced by individuals vary, and additional personal barriers frequently emerge [ 14 , 15 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PMR plan provided was 1200 calories per day (5020 kJ/day) for 12 weeks, which included meal replacement shakes or soups to cover two meals per day, and a third suitable simple meal option. The low-calorie meal replacement shakes (Example—in serving size: 54 g chocolate shake, 845 kJ energy, 3.3 g fat, 21.4 g carbohydrate and 20.1 g protein) used in this study were previously used in the DiRECT-Australia study [ 37 , 39 ]. These shakes/soups were provided free of cost to all participants by the research team.…”
Section: Methodsmentioning
confidence: 99%